2010
DOI: 10.1002/ffj.2019
|View full text |Cite
|
Sign up to set email alerts
|

A review on cyclodextrin encapsulation of essential oils and volatiles

Abstract: Cyclodextrins (CyDs) are cyclic carbohydrates derived from starch. The parent CyDs contain six, seven and eight glucopyranose units and are referred as a-, b-and g-CyD, respectively. The most important property of the CyDs is the ability to establish specific interactions -molecular encapsulation -with various types of molecules through the formation of noncovalently bonded entities, either in the solid phase or in aqueous solution. These nano-encapsulating agents may form inclusion complexes with essential oi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
360
0
18

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 578 publications
(409 citation statements)
references
References 112 publications
3
360
0
18
Order By: Relevance
“…Yeast extract source had a significant effect on chitinase production. [26,33,34] Shrimp shell waste containing chitin source was reported to be an important factor for chitinase production. [35] Gohel et al [36] has reported CaCl 2 as an influential media constituent for chitinase production by Pantoea dispersa.…”
Section: Selection Of Important Medium Components Using Plackettàburmmentioning
confidence: 99%
“…Yeast extract source had a significant effect on chitinase production. [26,33,34] Shrimp shell waste containing chitin source was reported to be an important factor for chitinase production. [35] Gohel et al [36] has reported CaCl 2 as an influential media constituent for chitinase production by Pantoea dispersa.…”
Section: Selection Of Important Medium Components Using Plackettàburmmentioning
confidence: 99%
“…In order to protect additives from temperature or light, encapsulation is a promising technique that can be used during film processing [58,59]. Liu et al investigated the applicability of gelatin-based films packaged with sunflower oil with different free/encapsulated tea polyphenol ratios through the synthesis of chitosan nanoparticles at 3 different encapsulation efficiencies (50%, 80% and 100%).…”
Section: Antioxidant Agentsmentioning
confidence: 99%
“…This way, the formation of inclusion complexes is result of an equilibrium between the free and CD molecules and the bioactive compounds-CD complex [99]. Therefore, some factors may affect inclusion complex formation, such as type of cyclodextrin, cavity size, pH and ionization state, temperature, and method of preparation [102].…”
Section: Cyclodextrinsmentioning
confidence: 99%
“…These inclusion complexes are relatively more hydrophilic and larger in size than the non-associated active compound, which helps to increase the retention of the encapsulated substance. They are also very interesting because they can mask undesirable flavors and odors that the encapsulated compounds may present [21,56,72,101,102,[106][107][108][109][110].…”
Section: Cyclodextrinsmentioning
confidence: 99%
See 1 more Smart Citation